2015
DOI: 10.1038/cddiscovery.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Factor VII promotes hepatocellular carcinoma progression through ERK-TSC signaling

Abstract: We previously demonstrated PAR2 starts upstreamed with tissue factor (TF) and factor VII (FVII), inhibited autophagy via mTOR signaling in HCC. However, the mechanism underlying for merging functions of PAR2 with the coagulation system in HCC progression remained unclear. The present study aimed to investigate the role of TF, FVII and PAR2 in tumor progression of HCC. The expressions of TF, FVII and PAR2 from HCC specimens were evaluated by immunohistochemical stains and western blotting. We found that the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Our previous work established a role for TF/FVII/PAR2 signaling in inhibition of autophagy and promotion of HCC tumor progression through activation of extracellular signal regulated kinase 1/2 (ERK1/2) and subsequently tuberous sclerosis 2 (TSC2)/mammalian target of rapamycin (mTOR). 21 , 22 , 23 We further showed that miR-135a expression was also dependent upon mTOR levels, as we observed decreased miR-135a in mTOR knocked-down Hep3B cells ( Figure 1 D). To corroborate the above correlations in a clinical setting, we compared FVII protein levels with miR-135a expression in HCC tissues.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Our previous work established a role for TF/FVII/PAR2 signaling in inhibition of autophagy and promotion of HCC tumor progression through activation of extracellular signal regulated kinase 1/2 (ERK1/2) and subsequently tuberous sclerosis 2 (TSC2)/mammalian target of rapamycin (mTOR). 21 , 22 , 23 We further showed that miR-135a expression was also dependent upon mTOR levels, as we observed decreased miR-135a in mTOR knocked-down Hep3B cells ( Figure 1 D). To corroborate the above correlations in a clinical setting, we compared FVII protein levels with miR-135a expression in HCC tissues.…”
Section: Resultssupporting
confidence: 53%
“…Tissue factor (TF) and factor VII (FVII) negatively regulate autophagy through signaling of the protease-activated receptor PAR2, responsible for malignant progression and decreased disease-free survival in HCC. 21 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…These data point to a complex and intimate receptor transactivation and autocrine signaling loop between TGF-β receptor/ALK5, PAR2, and EGFR in the regulation of RAS–MEK–ERK signaling. Prompted by the strong dependency of the migratory and many other TGF-β responses on PAR2 expression on the one hand [ 24 ], and on ERK activation on the other hand [ 9 ] in conjunction with the crucial role of ERK in PAR2-stimulated cell migration [ 21 , 22 , 23 , 30 , 31 ], we set out to test, mainly in PDAC-derived cells, whether recombinant human (rh)TGF-β1-triggered ERK activation depends on endogenous PAR2.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-associated inflammation especially procoagulant-driven inflammation is now widely recognized as one of key determinants of various type of cancer [27] , [28] , [29] , [30] , including HCC [31] , [32] , [33] . The transmembrane tissue factor (TF) triggers downstream signaling upon binding with blood coagulation factor VII (FVII) and transmitting signals through protease-activated receptors (PARs) activation, especially PAR2 [34] , [35] , [36] .…”
Section: Coagulant Microenvironment In Hccmentioning
confidence: 99%
“…A recent study also demonstrates that circular and local regional TF is overexpressed in HCC patients, and it is closely related to the invasive and metastasis indexes [52] . Our recent studies have demonstrated that activation of the TF/FVII/PAR2 axis is associated with increased migration and invasiveness in hepatoma cells in vitro [32] , [33] , [52] . This finding could be consistently observed in tumor tissues from HCC patients, where we found that increased FVII and PAR2 levels were significantly associated with clinical stage, increased invasion, and poor disease-free survival, however none of any significant association with TF expression.…”
Section: Coagulant Microenvironment In Hccmentioning
confidence: 99%